Analisis Resepsi terhadap Representasi Tokoh Disabilitas pada Film Agak Laen: Studi Resepsi Stuart Hall pada Penonton Film Agak Laen - Salsabila, Cintya; Febrianita, Roziana (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This research aims to find out how the audience's reception is related to the representation of disabled characters in the movie Agak Laen. The method used in this research is a qualitative research method by conducting in-depth interviews with the audience of the movie Agak Laen and documentation. With the discourse related to discrimination that has surfaced, the researcher wants to use a reception analysis to find out how the audience accepts the representation of disabled characters in the film Agak Laen. The results of the reception will then be classified into three positions of message reception according to Stuart Hall's theory, namely hegemony-dominant, negotiation, and oppositional. The results of this study show that the results of interviews with seven informants have different message acceptance. Two informants were in the hegemony-dominant position, two were in the negotiation position, and three were in the oppositional position. Based on the results of the research, it can be concluded that the representation of disability in the media, especially in movies, still does not represent people with disabilities in real life. The media is still fixated on stereotypes that have existed for a long time, so it rarely researches matters related to disability. With the variety of answers from the informants, it can also be concluded that each informant has a different acceptance based on their experience and knowledge.